2017
DOI: 10.1111/tmi.12843
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of HIV‐positive patients lost to follow‐up in African treatment programmes

Abstract: OBJECTIVE The retention of patients on antiretroviral therapy (ART) is key to achieving global targets in response to the HIV epidemic. Loss to follow-up (LTFU) can be substantial, with unknown outcomes for patients lost to ART programmes. We examined changes in outcomes of patients LTFU over calendar time, assessed associations with other study and programme characteristics and investigated the relative success of different tracing methods. METHODS We performed a systematic review and logistic random-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
113
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 55 publications
7
113
3
Order By: Relevance
“…Moreover, not all patients lost are successfully located. In a recent systematic review of tracing studies, we found that about 80% of patients could be located but this percentage varied widely across studies [21]. With the linkage data from South Africa this problem is less important: bias will only arise if patients with an ID differ systematically from those without ID and the effect of this bias cannot be minimised by the covariates included in the model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, not all patients lost are successfully located. In a recent systematic review of tracing studies, we found that about 80% of patients could be located but this percentage varied widely across studies [21]. With the linkage data from South Africa this problem is less important: bias will only arise if patients with an ID differ systematically from those without ID and the effect of this bias cannot be minimised by the covariates included in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Determinants of mortality were however similar for the 2012 and the current analysis, with high mortality rates in the first 6 months of ART and with low CD4 cell counts, which decreased with longer ART duration and higher CD4 cell counts. It would be worthwhile to examine trends over calendar years as recent studies have shown that in African programmes mortality among patients lost to follow-up appears to have declined in recent years [5,21]. This may be due to higher CD4 cell counts at the start of ART and to an increase in undocumented transfers to other clinics [5,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, although we made repeated attempts to contact those who were lost to follow-up, some of these may have died or transferred care causing misclassification. For example, a large meta-analysis found that 24% of HIV+ subjects lost to follow-up had self-transferred care and 34% had died 30 . Fourth, it is possible that differences in follow-up time at the UHI vs. regional centers may explain some of our findings regarding decentralized care, which should be clarified in subsequent analyses of the registry with longer follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent systemic review in 2017 suggests that more of sub-Saharan HIV-infected patients that are lost to follow-up are surviving better [59]. Also, the lack of postmortem studies in our program and the reliance on the verbal autopsy for children that died at home may have led to an inaccurate labeling of the cause of death in such cases.…”
Section: Limitations Of the Studymentioning
confidence: 99%